(untitled) (London Journal of Medical and Health Research, 2023)
Many medicinal plants have a significant effect upon the diseases, such as diabetes, skin, liver cancer, heart, respiratory, blood, and nervous system. Medicinal plants in Egypt contain a high concentration of secondary metabolites, according to suitable environmental conditions. The ancient Egyptians had written a lot of information about medicinal plants, their uses, and many drugs of these medicinal plants still used in medicine. Many medicinal plants are cleared on the wall of temples and in the papyri, famous Ebers papyrus that is written in 1550 B.C. cardiovascular diseases (CVD) defined according to the World Health Organization (WHO) as a defect of the circulatory system including heart and blood vessels. There are many types of CVD such as coronary heart disease (CHD), cerebrovascular disease, heart attacks, and strokes. The deposition of fatty substances, cellular waste, cholesterol, and other substances on the inner walls of blood vessels is the major cause of CVD, World Health Organization (2014). The aim of the present study is to clarification of some Egyptian medicinal plants for heart and, blood diseases such as Tropaeolum majus L. Uriginea maritima (L.), Salvia Species, Allium cepa and Allium sativum. The location, chemical components, active ingredients, and position of the effect of previous plants.